The Role of Education in Building Society - Hasanah, Rizwatul; Haryanto, Sigit (Proceedings International Conference on Education Innovation and Social Science, 2025)
These instructions give you basic guidelines for preparing papers for ICEISS 2023. Use the same font and size given in this template for each section. Abstract is in English covering the central issues of the study, the objectives, the methods/approaches and the results of the study. Abstract consists of one paragraph, not to exceed 250 words. [Sitka Banner 10, justified] One of the most significant aspects of human life is education. We can only transmit principles, ideas, attitudes, and social behaviors that represent a moral and honorable life through education. We cannot develop into civilized human beings without education. Humans have the ability to become intelligent and civilized beings through education. Education is essential to shaping people's personalities and determining how a community will develop. The contribution of education to the social, economic, and cultural progress of society is discussed in this article. By providing knowledge, skills, and moral and ethical values, education becomes the foundation for creating a competitive, tolerant, and civilized society. This study highlights the role of formal and non-formal educational institutions, as well as the importance of synergy between the government, educators, and the community in creating an inclusive and sustainable education system. Using a descriptive qualitative approach, this article shows that investment in education not only improves the quality of human resources but also strengthens social cohesion and national stability.